Conservative treatment of blunt hepatic trauma:my experience - Arora, Bhavinder K.; Arora, Rachit; Arora, Akshit (International Surgery Journal, 2016)
Background: Blunt hepatic trauma is common in abdominal injuries. In seventies different surgical procedures were evolved for operative treatment of liver injuries. In eighties the conservative treatment of liver injuries became the management of choice in hemodynamically stable patients. This study was conducted in patients of blunt hepatic trauma to assess the effectiveness of conservative treatment.to assess the effectiveness of conservative treatment. Methods: Two hundred patients with blunt hepatic trauma were included in this study. Clinical parameters, GCS and ISS were recorded in all the patients. FAST and CT scan were also done. Patients with unstable hemodynamics who responded to fluid challenge and with stable hemodynamics were included in conservative management of liver trauma. Results: In this study 200 patients were analyzed, 30 patients were operated due to unstable hemodynamics while 170 patients treated conservatively. Average numbers of blood units transfused were 2-3 units and average hospital stay was 4-7 days. The patient recovery is to the extent of 97% with a few complications only. Conclusions: The conservative treatment is safe option for blunt hepatic trauma patients in patients with stable hemodynamics. Intensive monitoring is essential as there may be failure in a few patients. The complication rate was minimum and no mortality.